express sinA in term cosA
Answers
Answered by
2
There you go :-
cos a = square root of (1- square of sin a)
tan = sin a / cos a = sin a/(square root of (1- square of sin a))
cosec a = 1/sin a
sec a = 1/cos a = 1/(square root of (1- square of sin a))
cot a = cos a /sin a = (square root of (1- square of sin a))/sin a
Mark as a brainliest
Answered by
2
Answer:
Step-by-step explanation:
cos a = square root of (1- square of sin a)
tan = sin a / cos a = sin a/(square root of (1- square of sin a))
cosec a = 1/sin a
sec a = 1/cos a = 1/(square root of (1- square of sin a))
cot a = cos a /sin a = (square root of (1- square of sin a))/sin a
sonabrainly:
mark it the brinaliest
Similar questions